Pengaruh Sumber Belajar Terhadap Hasil Belajar Pada Mata Pelajaran Ekonomi Kelas XI IPS di SMA Negeri 4 Kaur - Gemilang Aldi Perdana; Sazili Sazili; Rossa Ayuni (Universitas Dehasen Bengkulu, 2023)
This research aims to determine the effect of learning resources on learning outcomes in economics subjects in class XI social studies at SMAN 4 Kaur. The approach in this research is quantitative research. The population in this study were students majoring in social studies class XI at SMAN 4 Kaur with a sample of 32 people. Data collection techniques in this study were observation, questionnaires, and documentation. The data analysis technique uses averages, simple linear regression analysis, and the coefficient of determination uses SPSS version 29. The results of this study show that the average of Learning Resources at SMAN 4 Kaur is 46.65, which is in the 43-50 range. in the Very maximal category and the average of student learning outcomes is in the range of 83-91 which is in the good category. And from the results of data analysis, it shows that there is a significant influence from learning resources on learning outcomes of students majoring in social studies class XI at SMA Negeri 4 Kaur. The magnitude of the value of the coefficient of determination obtained results of 0.83 or 83%. With the meaning that the magnitude of the influence of the Learning Resources variable on learning outcomes is 83%. The deviation from linearity results obtained were F of 1.684 with a sig value. 0.640. Because the Sig value is > 0.005, it can be concluded that the line is linear.